2011
DOI: 10.1134/s1075700711030105
|View full text |Cite
|
Sign up to set email alerts
|

Forecast of global steel prices

Abstract: 304Economic forecasts rarely come true with a high degree of accuracy, however, this does not lead to the eradication of an interest in such forecasts. We can see an analogy with weather forecasts, which are frequently incorrect, but they do not express such a strong devia tion from the real weather as other forecast methods. Economic forecasts restrict the future ambiguity and thus promote more confident long term development strategies and investments. If one is to choose between a forecast and its absence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Given that values of MI are normalized to a scale of 100, +1% change in MI would lead to about +1.1% change in refined copper scrap supply. Previous work has shown that steel is price inelastic and the demand elasticity is in the range of −0.2 to −0.3 (Malanichev and Vorobyev, 2011). Therefore, based on the estimated price elasticity, we argue that refined copper scrap supply is price inelastic, and its main drivers are world GDP and level of mining activity.…”
Section: Refined Scrapmentioning
confidence: 74%
“…Given that values of MI are normalized to a scale of 100, +1% change in MI would lead to about +1.1% change in refined copper scrap supply. Previous work has shown that steel is price inelastic and the demand elasticity is in the range of −0.2 to −0.3 (Malanichev and Vorobyev, 2011). Therefore, based on the estimated price elasticity, we argue that refined copper scrap supply is price inelastic, and its main drivers are world GDP and level of mining activity.…”
Section: Refined Scrapmentioning
confidence: 74%
“…The design of another effective parameter (neuron number) on the GMDH model needs another parametric study. To do this, considering the previous studies (e.g., [21]), values of 2,4,6,8,10,12,14,16,18, and 20 were selected to be used as number of neurons in the parametric study and results of GMDH models based on R 2 are shown in Table 4. Among the obtained results, as it can be seen in Table 4, GMDH model number 8 with 16 neurons shows the best prediction performance and due to that neuron number of 16 was selected in the rest of modelling process.…”
Section: Group Methods Of Data Handlingmentioning
confidence: 99%
“…A major share of distributed iron ore is produced by the three companies of Vale (a semi-private company) (Rio de Janeiro, Brazil ), Rio Tinto(London, UK), and B.H.P Billiton(Melbourne, Australia). Because of the fact that each ton of crude steel is made by using 1.5 ton of iron ore, production of crude steel can be introduced as a demand agent and because provision of iron ore is almost exclusive, producers provide the market with an output totally in association with instant demand [10].…”
Section: Introductionmentioning
confidence: 99%
“…The global steel forecast model was tried by Malanichev and Vorobyev (2011) with multivariate regression using raw material costs and capacity utilization. In the research by Kapl and Müller (2010), the authors compared the efficiency of the autoregressive integrated moving averages (ARIMA) model with covariates versus multi-channel singular spectrum analysis (M-SSA).…”
Section: Literature Reviewmentioning
confidence: 99%